(untitled) (Journal of Informatics Education and Research, 2024)
This research aims to examine how Internet of Things (IoT) technology can be integrated into the process of creating smart cities. More precisely, the study will focus on the use of artificial intelligence (AI) and big data analytics in the development of sustainable urban environments. The need for innovative solutions that can efficiently manage resources and raise the standard of living for residents grows as urban regions expand. The goal of this project is to look into how the Internet of Things devices generate massive amounts of data that, when processed using advanced methods, could offer insightful information for decision-making. The study presents several case studies that show how improved approaches to waste reduction, energy management, and urban planning have been made possible by artificial intelligence-driven insights gleaned from the Internet of Things data. It also examines how these technologies might affect sustainability, focussing on the potential for resilient urban infrastructures that can change to meet shifting societal and environmental demands. This paper aims to synthesize existing research and practical applications to present a comprehensive overview of the revolutionary role that big data, artificial intelligence, and the Internet of Things (IoT) will play in shaping the future of sustainable urban development.